ORCHESTRATING AIRPORT STAKEHOLDER ON ONE ID INITIATIVE: A SERVICE SCIENCE PERSPECTIVE (The Indonesian Journal of Business Administration, 2019)
One ID initiative is a recommended practice from IATA that involved many stakeholders on the airport in order to provide seamless, secure passenger journeys through biometric recognition technology. AP2 as the airport operator has initiative to implement One ID on Soekarno-Hatta airport, Jakarta.Steps to achieve it are first situational analysis from Soekarno-Hatta Airport passenger process by using qualitative approach including benchmarking from Aruba Airport Happy Flow and Digi Yatra Program in Indian Airport, Focus Group Discussion on airport stakeholder and interview expert. Then analyzing the process model of value co-creation that including co-experience, co-definition, co-elevation and co-development. From the modelling, we could see the interactive relationship among airport stakeholders that involved on value co-creation process to realize One ID initiative. Value Orchestration Platform also modelled for orchestrating value co-creation process like involvement, curation and empowerment strategies.In this research, we use model value co-creation process and value orchestration platform as a hierarchical service by using service science perspective. We first examine and express the situation from Airport Passenger Processing in CGK Airport by using qualitative approach. Then, we analyze a process model of value co-creation consisting of four phases, i.e., co-experience, co-definition, co-elevation and co-development. The model describes interactive relationship among stakeholders in Airport by involving value co-creation process to supporting such collaboration. Finally, we apply three management strategies of value orchestration platform for orchestrating value co-creation process, i.e., involvement, curation and empowerment strategies. All the process will be organized on a Project Management Office.Keywords:  Biometric, Collaboration, Project Management, Service Science.